ANGULAR CORRELATION STUDIES IN OSMIUM 186 and OSMIUM 188 - King, William James (My University, 1958)
This thesis describes a series of experiments performed on two of the Osmium isotopes. From angular correlation studios carried out with a fast coincidence circuit, spins and parities have boon assigned to the seven lowest levels of Osmium 188 end the two known levels of Cs- mium 186. The results for the heavier isotope represent an extension of the decay scheme previously proposed by this laboratory and supported in part by other workers. For the lighter isotope the results give supporting evidence for assignments made using a less direct approach. The material presented here adds to the store of empirical Information concerning even-even nuclei at a tine when ouch knowledge is necessary for testing the predictions of various semi-empirical nuclear models
Keywords: Osmium; Isotopes; Multipole radiation; Nuclear spin; Shell Model